Assistance in the Preparation of Work Program Plan Documents for Village-Owned Enterprises (BUMDes) in Tanjung Batu District, Ogan Ilir Regency - Sunardi, Sunardi; Djazuli, Abid; Gusmiatun, Gusmiatun; Herudiyansyah, Gumar (Universitas Muhammadiyah Palembang, 2022)
The work program plan document is a requirement that must be met in the management of legal entities of Village-Owned Enterprises (BUMDes). Limited human resources cause the common control of BUMDes legal entities. The minimum competence to prepare a work program plan is understanding management and financial statements (accounting). In contrast, the conditions in the field of village BUM management mostly do not have these competencies, so the direction of legal entities is stopped. Tanjung Batu Subdistrict has 11 Village BUMDes, and 1 Village BUMDes has applied for a legal entity process. The activity focused on mentoring 5 Village BUM that had not yet submitted a legal entity process and was constrained by the work program plan document. The mentoring activity takes 12 hours, divided into three meetings, located at Pondok Tanjung Batu. The activity uses the participatory action research (PAR) method, involving BUMDes administrators and students. Activities are carried out in 3 stages, namely (1) preparation, (2) implementation of activities and (3) evaluation and closing. The results of the BUMDes work program preparation activities are carried out properly so that they are ready to take care of the legal bodies of each BUMDes